2007
DOI: 10.1111/j.1468-3148.2007.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Autism symptoms in toddlers with Down syndrome: a descriptive study

Abstract: Background-Research suggests that children with Down syndrome may be at increased risk of having an autism spectrum disorder; however, previous studies have not utilized comprehensive, state-of-the-art diagnostic tools to address the question of comorbid autism and Down syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 21 publications
6
40
2
Order By: Relevance
“…These figures are broadly consistent with the majority of previous prevalence estimates reported within the DS population (Capone et al, 2005;Hepburn et al, 2008;Kent et al, 1999;Lowenthal et al, 2007;Lund, 1988;Turk and Graham, 1997). However, they are higher than that reported by Gillberg et al (1986) and Ghaziuddin et al (1992) (both 5%) and lower than that reported by Starr et al, 2005 (39%).…”
Section: Prevalence and Profile Of Asd Symptomatology In Dssupporting
confidence: 92%
See 1 more Smart Citation
“…These figures are broadly consistent with the majority of previous prevalence estimates reported within the DS population (Capone et al, 2005;Hepburn et al, 2008;Kent et al, 1999;Lowenthal et al, 2007;Lund, 1988;Turk and Graham, 1997). However, they are higher than that reported by Gillberg et al (1986) and Ghaziuddin et al (1992) (both 5%) and lower than that reported by Starr et al, 2005 (39%).…”
Section: Prevalence and Profile Of Asd Symptomatology In Dssupporting
confidence: 92%
“…These findings are consistent with reports from Capone et al (2005), Carter et al (2007), Hepburn et al (2008) and Molloy et al (2009). A comparison of individuals with DS scoring above the cut-off for ASD with those meeting the more stringent criteria for autism was limited by the small sample size but indicated that those scoring above the cut-off for ASD only were more able than those who scored above the cut-off for autism.…”
Section: Prevalence and Profile Of Asd Symptomatology In Dssupporting
confidence: 92%
“…Additionally, an increasing incidence of individuals diagnosed with DS and comorbid 10 Daunhauer and Fidler autism has been reported in the literature (Dykens, 2007;Hepburn, Philofsky, Fidler, & Rogers, 2008;Kent, Evans, Paul, & Sharp, 1999). While once thought to occur at low rates in the DS population (1%-2%, see Dykens, 2007, for a review), currently, 5%-10% of children with DS also meet the criteria for autistic spectrum disorder (DiGuiseppi et al, 2010;Hepburn et al, 2008;Kent et al, 1999;Lowenthal, Paula, Schwartzman, Brunoni, & Mercadante, 2007). Below we address strengths and challenges in performance skills pertinent to occupational therapy practice.…”
Section: Client Factors: Body Functionsmentioning
confidence: 94%
“…ASD affects about 1 in 68 children (Centers for Disease Control and Prevention 2014) and is defined by deficits in sociocommunicative behaviors, the presence of odd or stereotypical behaviors, a restricted range of interests, and, sometimes, intellectual or language deficits. However, children with other developmental disabilities frequently display symptoms that overlap with those of children with ASD (Hepburn et al 2008;Klein-Tasman et al 2009), including significantly more behavioral and emotional problems than typically-developing peers (Baker et al 2003;Eisenhower et al 2005). Because symptoms associated with ASD vary in severity along a broad continuum, it is potentially helpful to study relations between the severity of these ASD-associated symptoms and parenting stress, as well as contributors to that stress, regardless of diagnostic classification.…”
Section: Introductionmentioning
confidence: 97%